Otimização para reduzir o tamanho de código-fonte JavaScript - Farzat, Fabio de Almeida (2018)
JavaScript is one of the most used programming languages for front-end development of Web application. The increase in complexity of front-end features brings concerns about performance, especially the load and execution time of JavaScript code. To reduce the size of JavaScript programs and, therefore, the time required to load and execute these programs in the front-end of Web applications. To characterize the variants of JavaScript programs and use this information to build a search procedure that scans such variants for smaller implementations that pass all test cases. We applied this procedure to 19 JavaScript programs varying from 92 to 15,602 LOC and observed reductions from 0.2% to 73.8% of the original code, as well as a relationship between the quality of a program’s test suite and the ability to reduce its size.